Use of Adjuvant Sorafenib in Liver Transplant Recipients with High-Risk Hepatocellular Carcinoma - Kirti Shetty; Chiranjeev Dash; Jacqueline Laurin (Journal of Transplantation)
The efficacy of liver transplantation (LT) for hepatocellular (HCC) is limited by tumor recurrence rates of 10–15%. We undertook this pilot study to examine the use of sorafenib as adjuvant therapy in high-risk LT recipients. Methods. We prospectively enrolled patients transplanted for HCC into a treatment protocol utilizing sorafenib if their explant examination showed evidence of viable tumor exceeding Milan criteria. We utilized as historical controls patients transplanted previously, whose explant tumor characteristics exceeded Milan criteria, but who were not “preemptively” treated with sorafenib. Wilcoxon two-sample test and Fisher’s exact test were used to compare survival and recurrence rates between the two groups. Results. Seven patients were treated with sorafenib and compared to 12 historical “controls.” Two of 7 treated patients suffered from HCC recurrence. Of the comparison group, 9 experienced HCC recurrence and all succumbed to disease. Dose reduction improved tolerance of drug. The overall rate of HCC recurrence was decreased in the adjuvant therapy group compared to historical controls (29% versus 75%, P=0.07). Disease free 1-year survival for the treated versus untreated group was 100% versus 66%, respectively. Conclusion. Adjuvant use of sorafenib is safe and decreases risk of HCC recurrence in high-risk LT recipients.